2005
DOI: 10.1108/13673270510602791
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, knowledge management, and sustained superior performance

Abstract: Purpose-This article attempts to begin the process of removing the cloak of causal ambiguity by examining the role that knowledge management has in the creation of the wide variety of competitive advantages found in some organizations. Specifically, this article aims to extend understanding in the field of knowledge management by examining how knowledge management can affect organizational performance, and by examining one possible determinant of an organization's capacity to manage knowledge. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(152 citation statements)
references
References 37 publications
7
141
1
3
Order By: Relevance
“…This finding is in line with the results of the study done by Abili and Zarekhalili (2014), Hoffiman et al (2005), and Khanifar (2011).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in line with the results of the study done by Abili and Zarekhalili (2014), Hoffiman et al (2005), and Khanifar (2011).…”
Section: Resultssupporting
confidence: 82%
“…Hoffiman et al (2005) have investigated the relationship between social capital and knowledge management and how knowledge management impacts organizational performance. The findings of their study shows that there is a significant relationship between social capital and knowledge management, and organizations with higher levels of social capital have more knowledge management compared with organizations with lower levels of social capital.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this test showed that organizations have no great potential in knowledge management and are on a continuum from levels 1 to 5. Hoffman et al (2005) in their study entitled "social capital, knowledge management and continuous superior performance" showed that organizations with high levels of social capital have greater capabilities in knowledge management than organizations with low levels of social capital. Agbo (2004) argues that knowledge management and intellectual capital in organizations are the key factors for success and innovation and effective management of knowledge assets include a holistic approach and educational programs should reflect the nature of innovation and dimensions knowledge management as very complex social processes.…”
Section: ) Organizational Culture Factorsmentioning
confidence: 99%
“…It also emphasizes social norms or general internalized sets of accepted behavior for members of the social network that enable participants to communicate their ideas and make sense of common experiences. Hence SC increases efficiency of action and reduce external unknowns (Hoffman et al, 2005). A fundamental benefit of neighborhood connections is that opportunities in various forms are generated through social networks (Anderson & Miller, 2003).…”
Section: Dimensions Of Social Capitalmentioning
confidence: 99%
“…This is very similar to the concept of informal social networks which refer to the relationships among social entities and the patterns and implications of these relationships . SC emphasizes information channels or social network that connect the organization to the outside world enabling it to maintain closure or the existence of sufficient ties to guarantee the observance of social norms (Hoffman, Hoelscher & Sherif, 2005). It also emphasizes social norms or general internalized sets of accepted behavior for members of the social network that enable participants to communicate their ideas and make sense of common experiences.…”
Section: Dimensions Of Social Capitalmentioning
confidence: 99%